Methotrexate Induces an Antioxidant Hormetic Response in Primary Rat Astrocytes - Armando Luna-López; Giovanna Adonahi Flores-González; Itzel Alejandra Rivera-Ruz; Raúl Librado-Osorio; Luis Alberto Erosa-De Haro; Mina Königsberg; Adriana Alarcón-Aguilar (SAGE Publishing, 2022)
Neurodegenerative diseases have increased worldwide in recent years. Their relationship with oxidative stress has motivated the research to find therapies and medications capable of suppressing oxidative damage and therefore slowing the progression of these diseases. Glutathione (GSH) is the most important cellular antioxidant in living beings and is responsible for regulating the cellular redox state. However, GSH cannot be administered by any route of administration, so molecules that increase its levels by activating Nrf2-ARE signaling pathway are explored; since Nrf2 regulates the main genes involved in GSH de novo synthesis and recycling. Astrocytes are the most important cell-type in the antioxidant cell response and are responsible for providing GSH and other substrates for neurons to have an efficient antioxidant response. Methotrexate (MTX) is an anti-inflammatory agent that has different cellular effects when administered at low or high concentrations. So in this study, we used MTX different concentrations and exposure times to induce a hormetic antioxidant response in rat primary astrocytes. Our results showed that 20 nM MTX pre-conditioning for 12 h augmented the GSH/GSSG ratio and protected cellular viability against a toxic MTX and H 2 O 2 insult, which was abrogated when Nrf2 was inhibited by brusatol. Hence, MTX subsequent studies as a drug to counteract the progression of some stress-associated neurodegenerative diseases are suggested.